Bilateral Coats' Disease Combined with Retinopathy of Prematurity. (30th August 2015) - Gursoy, Huseyin; Erol, Nazmiye; Bilgec, Mustafa Deger; Basmak, Hikmet; Kutlay, Ozden; Aslan, Huseyin
Abstract : Purpose . To report a case of bilateral Coats' disease combined with retinopathy of prematurity (ROP). Case . Retinal vascularization was complete in the right eye, whereas zone III, stage 3 ROP and preplus disease were observed in the left eye at 43 weeks of postmenstrual age (PMA) in a 31-week premature, 1200-g neonate. Intraretinal exudates developed and retinal hemorrhages increased in the left eye at 51 weeks of PMA. Diode laser photocoagulation (LP) was applied to the left eye. Exudates involved the macula, and telangiectatic changes developed one month following LP. Additional LP was applied to the left eye combined with intravitreal bevacizumab (IVB) injection at 55 weeks of PMA. Disease regressed one month after the additional therapy. At the 14-month examination of the baby, telangiectatic changes and intraretinal exudates were observed in the right eye. Diode LP was applied to the right eye combined with IVB injection. Exudates did not resolve completely, and cryotherapy was applied one month following LP. Retinal findings regressed three months following the cryotherapy. Conclusion . This is the first report of presumed bilateral Coats' disease combined with ROP. If Coats' disease could be diagnosed at early stages, it would be a disease associated with better prognosis.